2008
DOI: 10.1002/polb.21593
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpic relaxation of silica–polyvinyl acetate nanocomposites

Abstract: Although the effects of filler nanoparticles size and surface treatment on the glass transition temperature of the matrix phase have received well-deserved attention, nanofiller effects on other physical parameters associated with the glass transition have received less interest. To better understand how the incorporation of nanofillers affects the enthalpic relaxations associated with the glass transition, differential scanning calorimeter measurements were carried out on silica-polyvinyl acetate nanocomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
6
22
1
Order By: Relevance
“…The decrease in ΔH r occurred even though the suspensions had not been annealed below their T g , in contrast with previous results on silica/poly(vinyl acetate) nanocomposites. 62 In this latter case the nanoparticles affected the annealing peak only at long time scales, which the authors interpreted as a confirmation of the lack of an immobilized glassy layer at the surface of the particles, which otherwise should have given rise to measurable effects already at small annealing times. Nevertheless, the fact that ΔH r decreased with filler content for different annealing times and temperatures confirmed that the particles affected the molecular motion of the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in ΔH r occurred even though the suspensions had not been annealed below their T g , in contrast with previous results on silica/poly(vinyl acetate) nanocomposites. 62 In this latter case the nanoparticles affected the annealing peak only at long time scales, which the authors interpreted as a confirmation of the lack of an immobilized glassy layer at the surface of the particles, which otherwise should have given rise to measurable effects already at small annealing times. Nevertheless, the fact that ΔH r decreased with filler content for different annealing times and temperatures confirmed that the particles affected the molecular motion of the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the vast majority of experimental works reports a reduction 17,[43][44][45][46][47][48][49] or even a suppression 45,50,51 of physical aging. In this case, the vast majority of experimental works reports a reduction 17,[43][44][45][46][47][48][49] or even a suppression 45,50,51 of physical aging.…”
Section: Discussionmentioning
confidence: 99%
“…One consequence is an increase in the pressure-dependence of the dynamic crossover temperature, demarcating the onset of strong intermolecular cooperation of the dynamics. These results may be connected to the observation that filler slows the rate of structural relaxation in the glassy state; 62,63 such physical aging is governed by the loss of volume. Current efforts are directed to assessing whether the enhanced volume sensitivity of the segmental dynamics is a general phenomenon in filled polymers.…”
Section: Discussionmentioning
confidence: 99%